Policies of plant genetic resources for food and agriculture: China and the world: Report of a workshop, 1 December 2011, Beijing, China - Vernooy, Ronnie; Zhang Zongwen; Song Yiching; Bioversity International (2012)
This report summarizes the presentations and discussions of a diverse group of 20 researchers from academic institutions in China involved in national and international policy and law development related to agricultural biodiversity. Based on three field project experiences, the current institutional framework is reviewed, challenges are identified and recommendations made for changes.